Preconception care focusing on parenting preparedness among future parents: a scoping review - Sari , Siti Nurul Fadhilah; Astuti, Andari Wuri; Rosida, Luluk (Universitas Aisyiyah Yogyakarta, 2024)
Promoting preconception health care is a crucial public health strategy that promotes the development, growth, and well-being of child. However, awareness and knowledge of the importance of preconception care are still lacking among future parents. The purpose of this study was to identify information about implementation of preconception care focusing on parenting preparedness among future parents, including relevant sources of evidence from each article that has been found. The scoping review used the Arkey and O'Malley approach. Article search used three databases, such as PubMed, ScienceDirect and Wiley, published between 2019-2023. Results A total of 1,767 were then selected into 12 relevant articles. Several things that must be considered in providing preconception care in preparation for becoming parents to prospective bride and groom couples, namely the importance of physical, mental/psychological, and economic preparation and equality in sharing the role of parents in raising children. Creating good care for children is influenced by several factors, namely good knowledge, education, information access, and healthcare providers needed by prospective couples for providing preconception care in preparation for becoming parents. Examining policy frameworks that facilitate the provision of preconception care at local and national levels, including financing sources and provider guidelines, is necessary to improve understanding and implementation of effective preconception care strategies